Halal Investment Funds as Catalysts for Tourism Development: Analyzing Customer Trust, Religiosity, and Behavioral Intentions among Islamic Bank Clients in Saudi Arabia - Mokhtar Ahmed, Hebatallah Ahmed; Abdelhai Abdelghani, Abdelrahman Ahmed (CV. SPDF Harmony, 2025)
Background: Saudi Arabia’s Vision 2030 emphasizes economic diversification through Islamic finance and tourism, positioning halal investment funds as a strategic mechanism to channel ethical capital into sustainable tourism projects. Despite their growing prominence, the behavioral pathways through which fund attributes shape investment decisions remain insufficiently examined. Aims: This study investigates how key attributes of halal investment funds—Sharīʿah compliance transparency, tourism project alignment, ESG integration, and profitability history—affect customer investment intentions. It further explores the mediating roles of customer trust and perceived developmental impact, and the moderating effect of religiosity among Islamic bank clients. Methods: A quantitative, cross-sectional survey was conducted among 400 clients of three leading Islamic banks in Riyadh during April–May 2025. Validated scales were employed, and data were analyzed using structural equation modeling (SEM) with bootstrapping (5,000 resamples) to test direct, indirect, and moderated mediation effects. Result: The findings demonstrate that halal fund attributes significantly enhance investment intentions (β = 0.312, p < 0.001). Both customer trust (β = 0.198, p < 0.001) and perceived developmental impact (β = 0.156, p < 0.001) partially mediated this relationship. Religiosity acted as a significant moderator, strengthening these effects among highly religious clients. The model accounted for 62.3% of the variance in investment intentions, indicating substantial explanatory power. Conclusion: Halal investment funds, when characterized by transparent Sharīʿah governance and demonstrable developmental contributions, can effectively mobilize Islamic capital for tourism under Vision 2030. Fund managers should emphasize ESG integration and tourism-linked benefits, while tailoring communication to varying levels of religiosity. The results provide both theoretical advancement for Islamic finance literature and practical guidance for policymakers and industry stakeholders in sustainable tourism development.